Assisting the Evaluation of Merdeka Curriculum Implementation in Science Learning - PRELIA DWI AMANAH (Postgraduate Program, University of Mataram, 2026)
The implementation of the Merdeka Curriculum requires the readiness of teachers, schools, and evaluation systems that are capable of ensuring the realization of student-centered learning. This community service activity aims to describe the implementation of the Merdeka Curriculum in science learning and to evaluate various challenges that arise during its implementation at SMPIT ABATA Lombok. The method employed in this activity was a descriptive qualitative approach, conducted through classroom observations, in-depth interviews, and reflective discussions with the school principal and science teachers. The results of the activity indicate that the Merdeka Curriculum provides teachers with greater flexibility in designing contextual and creative learning experiences. However, several challenges were identified, including limited laboratory facilities, variations in students’ abilities, and differences in the levels of technological literacy among teachers. The evaluation of curriculum implementation was conducted using the CIPP (Context, Input, Process, Product) evaluation model, which enables a comprehensive assessment of the learning process. This activity contributes to improving teachers’ understanding of curriculum implementation and encourages stronger collaboration among teachers in developing more innovative science learning practices.